Kinerja Dinas Tenaga Kerja dan Sertifikasi Kompetensi dalam Pelayanan Penempatan Tenaga Kerja di Kota Denpasar - Destyawati, Ni Putu Erika; Yudartha, I Putu Dharmanu; Putri Wirantari, I Dewa Ayu (CITIZEN CHARTER, 2019)
ABSTRACT Denpasar is the region with the highest population in the Province of Bali. Due to the large number of population, it will affect the number of job seekers in an area. Therefore, Denpasar has to deal with unemployment issues, The Department of Labor and Denpasar Competency Certification has made efforts to overcome this issue by running the employment placement services. This study aims at finding the performance of the Department of Labor and Competency Certification of Denpasar in employment placement services. The results of this study showed that the performance of The Department of Labor and Denpasar Competency Certificationis good enough. It indicates good human resources and infrastructure, well-responded to any complaints, have achieved the target even though the numbers are unstable and able to be responsible and report all activities both in the internal and external environment of the organization. Keywords : Employment, performance, employment placement services